Comprehensive reparation for victims: Approach to its historical evolution. - Alvarado Moncada, Zoila; Cevallos Sánchez, Gissela (Revista Universidad de Guayaquil, 2023)
The present investigation was aimed at analyzing the historical background of the comprehensive reparation of the victims, from the perceptions of Hebrew Law, Roman Law, Hispanic Canon Law and Indian Law, as well as from continental European and Latin American Law. The methodology used was documentary, descriptive and the Analytical-Synthetic and Historical-Logical methods were used. Likewise, the review of various bibliographic sources allowed the development of an exhaustive analysis of the subject of study, considering various approaches that have strengthened the right to comprehensive reparation. Therefore, based on the documentary development and the revision of international legislation, the development of doctrinal and legal contents in which essential principles of law converge, such as the victimological and restorative justice elements that allow adhering to a perspective, has become evident. broad and comprehensive approach to repairing the most challenging problems. Therefore, the reparation of the victim has become a forceful figure, inalienable and not subject to economic or political relativity, since even in the face of the material incapacity of the perpetrator or his lack of will, the State must guarantee reparations in which must converge the necessary aspects to guarantee the rights of the victims.